IMPLEMENTASI MESIN PRESS MEDIA TANAM UNTUK PENINGKATAN EKONOMI MASYARAKAT DUSUN KARYA TANI MELALUI PEMANFAATAN COCOPET DAN LIMBAH SEKAM PADI - Imansyah, Fitri; Wahyudi, Tri; Wijayanto, Dedi (Jurnal Abdi Insani, 2024)
Coconut fiber waste processed into cocopeat can be an excellent growing medium. The management of scattered coconut fiber waste, which can only spoil the surrounding environment, requires innovation and technological renewal capable of compacting cocopeat into a highly useful and economically valuable growing medium. The production of growing media involves adding rice husk charcoal, husk, and burnt soil in an environmentally friendly manner. The cocopeat pressing machine can be used to facilitate farmers' work, making it more effective and efficient, thus addressing the problem of cocopeat waste and turning it into a growing medium that can increase the income of coconut farmers. The aim of this program is to improve the economy of the Dusun Karya Tani community through the implementation of a growing media press machine by utilizing cocopeat and rice husk waste. This program involves several key stages: needs identification and planning, procurement and installation of the press machine, technical and business management training, production and marketing, and monitoring and evaluation. The results of this program show a significant increase in community knowledge and skills related to the operation of the press machine and business management. Production of growing media increased from 50 kg to 300 kg per week, with better and more consistent product quality. This production increase directly impacts community income, rising from IDR 500,000 to IDR 2,500,000 per month. Besides the economic impact, the program also provides social and environmental benefits. The utilization of agricultural waste reduces the amount of unmanaged waste, while increased community involvement in productive economic activities helps reduce unemployment rates. Program evaluation indicates the need for further training and periodic assistance to ensure program sustainability.